Gap-Balancing versus Measured Resection Technique in Total Knee Arthroplasty: A Comparison Study - Churchill, Jessica L.; Khlopas, Anton; Sultan, Assem A.; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2018)
Proper femoral component alignment in the axial plane during total knee arthroplasty (TKA) depends on accurate bone cuts and soft tissue balancing. Two methods that are used to achieve this are “measured resection” and “gap balancing.” However, a controversy exists as to which method is more accurate and leads to better outcomes. Therefore, the purpose of this study was to evaluate: (1) implant survivorship, (2) patient outcomes, (3) complications, and (4) radiographic analysis comparing patients who underwent TKA with either gap-balancing or measured resection techniques. A total of 214 consecutive patients (221 knees) underwent primary TKA by a single surgeon between 2011 and 2012. Component alignment was achieved by using measured resection in 116 knees and gap balancing was used in 105 knees. The patients had a mean age of 66 years (range, 44–86 years) and a mean body mass index of 32 kg/m2 (range, 22–52 kg/m2). Patient range-of-motion (ROM) and Knee Society (KS) function and pain scores, and radiographic assessment, were assessed preoperatively and postoperatively at ∼6 weeks, 3 months, 1 year, and then annually. The mean follow-up time was 3 years. A Kaplan–Meier's analysis was performed to calculate the survivorship. The aseptic survivorship was 98% in both the measured resection and gap-balancing groups. The mean ROM was not significantly different between the measured resection and gap-balancing groups (123 vs. 123 degrees, p = 0.990). There were no significant differences between the two groups in terms of the KS function scores (86 vs. 85 points, p = 0.829) or the KS pain scores (93 vs. 92 points, p = 0.425). Otherwise, the radiographic evaluation at latest follow-up did not demonstrate any evidence of progressive radiolucencies or loosening, of any prosthesis. The results of this study found that at a mean follow-up of 3 years, both the measured resection and gap-balancing techniques achieved excellent survivorship and postoperative outcomes. This demonstrates that both methods can be used to achieve accurate femoral component alignment with similar short-term outcomes.
Keywords: gap balancing; total knee arthroplasty; component alignment; measured resection